A Three Dimensional Multi‐Layered Sliding Triboelectric Nanogenerator. Issue 11 (9th April 2014) - Du, Weiming; Han, Xun; Lin, Long; Chen, Mengxiao; Li, Xiaoyi; Pan, Caofeng; Wang, Zhong Lin
<x xml:space="preserve">Abstract</x> A novel design of a 3D triboelectric nanogenerator (TENG) is demonstrated. Because of its largely increased friction areas, the device has a multi‐layered structure, high transferred‐charge‐quantity, and current output. It delivers an open‐circuit voltage of 800 V, a short‐circuit current density of 5.5 mA m‐2 with a maximum instantaneous power of 4.4 W m‐2. This represents important progress toward practical applications in self‐powered technologies. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>